2008
DOI: 10.1016/j.juro.2007.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Ileal Enterocystoplasty and B12 Deficiency in Pediatric Patients

Abstract: Pediatric patients who have undergone ileal enterocystoplasty are at risk for development of vitamin B12 deficiency. These patients are at the highest risk beginning at 7 years postoperatively, and the risk increases with time. We recommend an annual serum B12 value in children beginning at 5 years following bladder augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 12 publications
2
16
0
2
Order By: Relevance
“…A low vitamin B 12 level was defined as ,300 pg/mL. [1][2][3][4] An ABX Pentra 120 (Horiba) device was used for the blood count, and a Roche E-601 analyzer was used for the detection of vitamin B 12 levels.…”
Section: Methodsmentioning
confidence: 99%
“…A low vitamin B 12 level was defined as ,300 pg/mL. [1][2][3][4] An ABX Pentra 120 (Horiba) device was used for the blood count, and a Roche E-601 analyzer was used for the detection of vitamin B 12 levels.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with hypocobalaminemia may present with pernicious anemia, characterized by megaloblastic anemia, gastrointestinal symptoms, and potentially irreversible neurological symptoms including peripheral neuropathy, loss of positional and vibrational sense, ataxia, seizures, and dementia (58,59). The risk of hypocobalaminemia is thought to increase approximately 5 years after augmentation and continues to escalate over time (60,61).…”
Section: Vitamin B12 Deficiencymentioning
confidence: 99%
“…They recommended vitamin B12 replacement for patients losing more than 50 cm of terminal ileum starting 1 year after surgery. Rosenbaum et al [18] found that pediatric patients who had undergone ileal enterocystoplasty were at the highest risk of developing vitamin B12 deficiency 7 years postoperatively, and that the risk increased with time. They recommended an annual serum vitamin B12 value in children beginning 5 years postoperatively.…”
Section: Ileum and Colonmentioning
confidence: 99%